Handbook of International Trade, Volume II
DOI: 10.1002/9780470757697.ch12
|View full text |Cite
|
Sign up to set email alerts
|

Modern Commercial Policy: Managed Trade or Retaliation?

Abstract: In this paper we study worldwide antidumping (AD) case filing patterns in order to determine the extent to which economic versus strategic incentives explain the behavior of countries employing AD actions. We compare four main hypotheses: big supplier, big change in imports, tit-for-tat and the club effect. We find strong support that AD actions are directed at big suppliers, but far weaker evidence that AD actions are filed against suppliers whose imports have surged. We also find very strong evidence that AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…We will thus show that the introduction of asymmetry makes it possible for governments to enhance their cooperation, so that retaliation is welfare enhancing. 25 To show this result formally in our model, we introduce one modi…cation throughout this section: in order to obtain clear closed-form solutions, we assume a continuum of types. 26 Hence, governments are assumed to draw a political preference parameter from a continuous distribution with support = [ 1 ; N ] and uniform density g.…”
Section: An Intuitive Mechanism Of Welfare-enhancing Retaliationmentioning
confidence: 99%
“…We will thus show that the introduction of asymmetry makes it possible for governments to enhance their cooperation, so that retaliation is welfare enhancing. 25 To show this result formally in our model, we introduce one modi…cation throughout this section: in order to obtain clear closed-form solutions, we assume a continuum of types. 26 Hence, governments are assumed to draw a political preference parameter from a continuous distribution with support = [ 1 ; N ] and uniform density g.…”
Section: An Intuitive Mechanism Of Welfare-enhancing Retaliationmentioning
confidence: 99%
“…4 For example, Blonigen and Brown (2003) find that industries with export exposure are less likely to file and Prusa and Skeath (2004) provide evidence of titfor-tat retaliation to AD petitions. 5 On the basis of the investigation record, the International Trade Commission found that Weldbend was not an importer or exporter of the product or the components of the product or affiliated in any way with a corporate entity that was involved in trading the product internationally (U.S.…”
Section: The Modelmentioning
confidence: 97%
“…On the one hand, country i may reduce AD against country j for fear of retaliation (Feinberg and Reynolds, 2006). On the other hand, as an AD club member, country j is more likely to be targeted, a result captured by the "AD club" effect (Prusa and Skeath, 2004). Therefore, the influence of CLUB is ambiguous.…”
Section: Empirical Strategy and Datamentioning
confidence: 99%